Emerging hydrogel therapies for translating brain disease: Materials, mechanisms, and recent research - Xinyu Lu; Yi Luo; Xiaochun Hu; Jianjian Chu; Siqi Li; Mengqi Hao; Jianhua Zhuang; Yan Liu; Jie Gao; You Yin (Materials Today Advances, 2024)
Brain diseases, encompassing neurodegenerative disorders, strokes, and brain tumors, represent significant medical conditions with profound implications for human health. The blood-brain barrier (BBB) and the blood-cerebral-spinal cord barrier (BCSFB) limited drug penetration, poor drug targeting, and limited proliferation and easy death of mature neuronal cells greatly impair regeneration of the central nervous system after the injury, and thus call for more advanced therapeutic strategies in the clinic. Biomedical hydrogel research presents a potentially novel therapeutic approach for the management of brain disorders. Hydrogels are extremely biocompatible scaffolding materials that can be loaded with a variety of drugs for achieving effective treatments for brain disorders and can be customized with different mechanical properties to match the target organ or modulate its environment. This article offers an overview of recent research progress, challenges, and prospective developments in the utilization of hydrogels for treating brain disorders, with the objective of accentuating their potential as an early intervention in the preclinical phase. The unique mechanisms of drug release in hydrogels are examined in detail: extended-release medications, environmental release of drugs, and the material's own activity. An understanding of these mechanisms helps to make more effective drug delivery systems to the brain possible.